Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - and Green, Duncan; Guijt, Irene (Itad, Oxfam and IDS, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery